Study of some antimicrobial agents produced by actinomycetes and its effect on bacteriospermia - Ayat Saied Saad Hamza; Doaa Ghaith; Eman Anwar Mohammed Hassan; Mohamed Ez Eldeen Abdelhaleem Dawoud (Cairo : Ayat Saied Saad Hamza, 2020)
150 samples were examined from infertile men patients (age: 20-65), attending the International Islamic Center for Population Studies and Research Center (IICPSR), El-Hussein Teaching hospitals, Faculty of Medicine, Al- Azhar University, Cairo, Egypt, during May 2016 to October 2016. 150 samples were examined for culture and sensitivity of seminal fluid under aseptic condition within 1 hour of the seminal fluid collection. It was found 88 (58.7%) sample positive for bacterial growth, and 62 samples (41.3%) showed no growth. 88 samples show growth of bacteria on culture media, of them 30 samples defined by identification method (morphology and biochemical reaction tests) as Staphylococcus aereus represent the most frequent bacteria identified (20 % of the whole study samples), 21 samples defined as Escherichia coli (14 % of the whole study samples), 11 samples defined as Proteus sp (7.3 % of the whole study samples, 10 samples defined as Klebisilla sp (6.7 % of the whole study samples), 9 samples defined as Serratia sp (6 % of the whole study samples) and 7 samples defined as Enterococcus feacalis (4.7 % of the whole study samples). Sensitivity tests were done for infected samples using artificial traditional antibiotics to detect the broad spectrum of artificial antibiotics which can be active against all the obtained bacterial growth. Sensitivity tests of 20 traditional artificial antibiotics showed that,there are 5 antibiotics react with all the examined bacterial growth ; (Ampicillin_AM10og, Cloxacillin_OB5og, Kanamycin_K30og, Nalidixic Acid_NA30og and Ofloxacin_Ofx20 og)
Thesis (M.Sc.) - Cairo University - Faculty of Science - Department of Botany - Microbiology
Issued also as CD
Keywords: Actinomycetes; Antimicrobial agents produced; Bacteriospermia